Validation of the AASLD recommendations for classification of oesophageal varices in clinical practice. (8th December 2019) - Fateen, Waleed; Ragunath, Krish; White, Jonathan; Khanna, Amardeep; Coletta, Marina; Samuel, Sunil; Ortiz, Jacobo; James, Martin; Wilkes, Emilie; Aithal, Guruprasad P.; Guha, Indra N.; Sami, Sarmed S.
Abstract: Background & Aims: The American Association for the Study of Liver Diseases recommends the use of a 2‐grade classification system (small and large) to describe the size of oesophageal varices (OV). Data on observer agreement (OA) on this system are currently lacking. We aimed to evaluate this classification and compare it to the widely used 3‐grade classification (grade 1 'small', grade 2 'medium', grade 3 'large') among operators of variable experience. Methods: High‐definition video recordings of 100 patients with cirrhosis were prospectively collected using standardised criteria. Nine observers of variable experience performed independent evaluations of the videos in random order. OV were scored using both systems. All assessments were repeated a year later by the same observers to assess intra‐observer agreement. Results: Interobserver agreement (all observers) using the 2‐grade and the 3‐grade system was k = 0.71 (95% CI: 0.64‐0.78) and k = 0.73 (95% CI: 0.66‐0.79) respectively. When using the 2‐grade system, intra‐observer agreement between hepatologists (n = 3), luminal gastroenterologists (n = 3) and trainee gastroenterologists (n = 3) was k = 0.89 (95% CI: 0.86‐0.91), k = 0.72 (95% CI: 0.67‐0.77), and k = 0.74 (95% CI: 0.67‐0.8) respectively. With the 3‐grade system; intra‐observer agreement between the same three subgroups were k = 0.9 (95% CI: 0.87‐0.92), k = 0.73 (95% CI: 0.68‐0.78), k = 0.77 (95% CI: 0.71‐0.82) respectively. Conclusions: There was no difference in OA between the 2‐grade and 3‐grade classification systems. Hepatologists had significantly higher levels of consistency in grading OV. This may have implications to create alternative training models for residents and fellows in the recognition and grading of OV. Abstract : See Editorial on Page 754